Psychological explanation : the influence of the "orthodox" view of science of psychology - MacKay, Nigel (Department of Psychology, 2026)
It is characteristic of science and art and other exercises of the human mind, practical and theoretical, that they may be profoundly influenced by doctrines and ideas that originate at some distance from them. Often the assumptions an determining philosophies that back up the practices of a science remain tacit and unacknowledged, hidden perhaps from even those who operate under their influence. Psychology shares these characteristics. The methods and theories of behavioural science are more than convenient ways of handling and expressing psychological facts. They are the exercise of philosophical preconceptions about humans, and ideas about the kind of knowledge that may be gained of their activities.